2012
DOI: 10.1002/ange.201203847
|View full text |Cite
|
Sign up to set email alerts
|

Einfach und dennoch herausfordernd: Neues zur asymmetrischen Synthese von Spiroketalen

Abstract: Spiroketale sind in Naturstoffen häufig vorkommende Strukturelemente. Nicht selten sind sie die pharmakophoren Gruppen, die die biologischen Eigenschaften der Verbindungen maßgeblich bestimmen. Die Vielfalt reicht von einfachen chiralen Verbindungen bis zu komplexen Spiroketalpolyketiden, z. B. Reveromycin B (1).[1] Spiroketale mit anellierten aromatischen Gruppen (hier verkürzt: aromatische Spiroketale) sind als Bestandteile von Naturstoffen deutlich seltener, aber es gibt sehr prominente und interessante Bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The latter method was used in one of the shortest and most efficient reported synthesis of strychnine, which was reported in Angewandte Chemie 2a. He recently wrote a Highlight on the stereoselective synthesis of spiroketals 2b. Reissig was a member of the Editorial Board of Liebigs Annalen and subsequently the International Advisory Board of European Journal of Organic Chemistry from 1995–2008…”
Section: Awarded …︁mentioning
confidence: 99%
“…The latter method was used in one of the shortest and most efficient reported synthesis of strychnine, which was reported in Angewandte Chemie 2a. He recently wrote a Highlight on the stereoselective synthesis of spiroketals 2b. Reissig was a member of the Editorial Board of Liebigs Annalen and subsequently the International Advisory Board of European Journal of Organic Chemistry from 1995–2008…”
Section: Awarded …︁mentioning
confidence: 99%
“…hydroxy group in trapping the cation and forming a spiroketal (6). [7] This sequence, which we called hydride-shift-initiated spiroketalization, would be another potentially general piece of methodology for organic synthesis.Initial results strongly suggested that the success of the hydride shift depended on the relative configuration between the exocyclic hydroxy group (activated as a leaving group) and the ring junction. [8] Moreover, previous experiments with deuterium labeling at the ring junction showed convincingly the intramolecular nature of this hydride shift.…”
mentioning
confidence: 99%
“…hydroxy group in trapping the cation and forming a spiroketal (6). [7] This sequence, which we called hydride-shift-initiated spiroketalization, would be another potentially general piece of methodology for organic synthesis.…”
mentioning
confidence: 99%